2019
DOI: 10.1038/s41419-019-2164-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 alleviates doxorubicin resistance in breast cancer through inhibition of epithelial-mesenchymal transition by targeting DUSP4

Abstract: Acquired resistance to chemotherapy is a major obstacle in breast cancer (BC) treatment. Accumulated evidence has uncovered that microRNAs (miRNAs) are vital regulators of chemoresistance in cancer. Growing studies reveal that miR-137 acts as a suppressor in tumor progression. However, it remains obscure the role of miR-137 in modulating the sensitivity of BC cells to doxorubicin (DOX). In this study, we demonstrate that miR-137 exerts a significant effect on repressing the development of chemoresistance of BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…Western blot analysis was performed as described previously [35][36][37] . Anti-PIK3R5, N-cadherin, E-cadherin, Vimentin, MMP2, Beclin1, p62, ATG5, LC3-II, Bax, Bcl2, cleaved caspase-3, and GAPDH were purchased from Abcam (Cambridge, UK), and anti-p-AKT, AKT, p-mTOR, and mTOR were obtained from Cell Signaling Technology.…”
Section: Western Blotmentioning
confidence: 99%
“…Western blot analysis was performed as described previously [35][36][37] . Anti-PIK3R5, N-cadherin, E-cadherin, Vimentin, MMP2, Beclin1, p62, ATG5, LC3-II, Bax, Bcl2, cleaved caspase-3, and GAPDH were purchased from Abcam (Cambridge, UK), and anti-p-AKT, AKT, p-mTOR, and mTOR were obtained from Cell Signaling Technology.…”
Section: Western Blotmentioning
confidence: 99%
“…Then we looked back ΔNp63α-induced EEC-transcriptomes, and found that DUSP4 was one of the most upregulated gene, and it was known to be an important EMT promoting molecule 27,28 . To verify the promoting effect of ΔNp63α on the expression of DUSP4, we measured the protein level of DUSP4 in EECs infected with Ad-ΔNp63α, and found that DUSP4 protein was elevated by 1.5-fold (Fig.…”
Section: δNp63α Induces Dusp4 Downregulated Gsk3β Expression In Eecsmentioning
confidence: 99%
“…Since circASPH was determined to be a sponge of miR-370, we postulated that circASPH positively regulated HMGA2 by sponging miR-370. Generally, miRNAs regulate the posttranscriptional expression of target genes by specifically binding to the 3′-untranslated regions (3′-UTRs) 28 . Using TargetScan, we found a potential target site of miR-370 on the 3′-UTR of HMGA2 mRNA (Fig.…”
Section: Circasph Modulates the Expression Of Hmga2 A Direct Targetmentioning
confidence: 99%